Pengembangan Buku Cerita Rakyat Sumbawa: “Lalu Dia Lala Jinis” Dalam Mata Pelajaran Bahasa Indonesia - Sunia Tri Putri; Moh. Irawan Zain; Safruddin (Journal of Classroom Action Research, 2022)
This research and development was carried out against the background of the reality on the ground that there were no local wisdom-based textbooks, especially Sumbawa folklore, which were in accordance with the competencies to be achieved. In the conditions of people's lives that are experiencing a moral crisis, literature can actually be used as a 'helper' because learning literature besides being able to help students love to read and write, can also be used as a means to improve students' personalities. This study aims to describe the validity of the Sumbawa folklore book model "Lalu Dia Lala Jinis", determine the legibility of Sumbawa folklore books, and determine the feasibility of the Sumabawa folklore book "Lalu Dia Lala Jinis" in class students at SDN Brang Biji. The research method used in the research is research and R&D (Research and Development) with the ADDIE development model design. The steps for developing the ADDIE model include the stages of Analysis, Design, Development, Implementation, Evaluation. Data collection methods used in the form of questionnaires and study documentation. The subject of this research is the fifth grade students of SDN Brang Biji, Sumbawa Regency. The validity test of folklore books was carried out by two media experts and material experts. The legibility test of folklore books was carried out by fifth graders at SDN Brang Biji. The results showed that the Sumbawa folklore book "Then Dia Lala Jinis" was feasible and effective to be used as a learning medium, as seen from the results of media expert validation getting a percentage of 92%, material expert validation getting a percentage of 82%, and student responses to the use of the book getting percentage 98%.